High precision Faraday collector MC-ICPMS thorium isotope ratio determination - Potter, E; Stirling, C; Andersen, M; Halliday, A (2005)
Uranium-series dating of carbonate materials requires precise determination of the spike sample thorium isotope ratio, 230Th/229Th. This ratio is commonly measured using ion counting techniques, however the precision of analyses using ion counting devices suffers from beam intensity limitations, drift in multiplier gain and non-linearities in electron multiplier response. Here, we describe the application of multiple-collector inductively coupled plasma mass spectrometry (MC-ICPMS) to determine thorium isotope ratios at hitherto unattained precision. For the first time, thorium isotope analyses were performed using only Faraday collectors coupled to 1011 Ω feedback resistors in the amplifier system. Spiked thorium solutions were concentrated to produce 230Th and 229Th signal intensities of around 50 mV and 100 mV, respectively (across a 1011 Ω resistor) and are run at high intensity for a short period of time (∼1 min). These analyses yield a 230Th/229Th external reproducibility of better than 0.3‰ for ∼25-30 pg of consumed 230Th. This is a factor of two better than the best published thermal ionisation mass spectrometry (TIMS) and MC-ICPMS techniques for similar sample sizes, and represents up to an order of magnitude improvement over many other established protocols. Combined with new techniques for high precision Faraday measurement of uranium isotopic composition [1], this permits improvements in the uncertainty of U-series ages to better than 0.1 thousand years (ka) at 100 ka and 1 ka at 300 ka. It should also be possible to resolve events to ∼14 ka at 600 ka. Using these techniques, the U-series dating limit can be extended from 500-600 ka to 800 ka enabling a more detailed study of the frequency of late Pleistocene climate events. © 2005 Elsevier B.V. All rights reserved.